Effect of crop establishment methods and phosphorus nutrition on growth and productivity of mungbean (Vigna radiata L. Wilczek) in semi-arid Afghanistan - Ehsan, Qudratullah; Rana, D.S.; Choudhary, Anil K. (Annals of Agricultural Research, 2017)
A field experiment was conducted at Experimental Farm of Afghanistan National Agricultural Sciences and Technology University (ANASTU), Kandahar, Afghanistan during July to September, 2015 comprised of 8 treatment combinations using two planting methods (broadcast and line-sowing) and four phosphorus levels (0, 30, 60 and 90 kg P2O5 ha–1) in a sandy-clay loam soil to assess the growth, morpho-physiological and yield parameters, and yield of mungbean in a split-plot design replicated thrice. It was revealed that line-sowing exhibited significantly higher values of growth parameters (plant height, leaf area index, dry matter accumulation, branches plant–1), growth indices (absolute growth rate, crop growth rate, relative growth rate, net assimilation rate), root growth parameters (root dry weight plant–1, root nodules plant–1 and root length plant–1), yield attributes, and grain (1284 kg ha–1) and straw yield (2943 kg ha–1) of mungbean over broadcast-sowing. Likewise, the successive increase in phosphorus levels upto 60 kg P2O5 ha–1 resulted in significantly higher growth attributes, growth indices, root growth parameters, yield attributes and grain and straw yield of mungbean compared to rest of the P2O5 levels. In general, the highest grain yield (1420 kg ha–1) recorded with 60 kg P2O5 ha–1 which was 8.5, 7.6 and 67.5% higher over 30 kg P2O5 ha–1, 90 kg P2O5 ha–1 and control, respectively. Overall, line-sowing alongwith 60 kg P2O5 ha–1 can be recommended to harness higher growth and productivity of Kharif mungbean in semi-arid conditions of Afghanistan.